Arabilitas: A Web-Based Arabic Learning Application and Teaching Material for Visually Impaired Students in Higher Education - Alhamuddin, Alhamuddin; Nurhakim, Haditsa Qur’ani; Adawiyah, Rabiatul; Fanani, Ahmad (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to design learning media in the form of Web Accessible for blind students. This is done to help blind students understand the material with learning media that suits their characteristics. This research considers the experience of blind students in implementing online learning in higher education and their needs for learning media in the form of Elearning. The results of the data collection will be used as recommendations for developing learning media that can help blind students in online learning in higher education. This research emphasizes that the features that must be present in the learning media must answer the obstacles faced by blind students in online learning in higher education. Web Arability is the answer to help the difficulty of learning Arabic. The result is an increase in understanding in learning Arabic when using Web Arabilitas.